(untitled) (LACCEI, 2024)
In this article, the automation of a bottling plant in northern Peru is presented with the aim of improving efficiency and productivity. The main problem identified in the plant was the lack of use of any simulation software to analyze possible events in the production area, as all processes were performed manually. In order to resolve this problem, the ProModel programming software was used to analyze factors such as the number of operators, locations and entities. The simulation allowed for a better outcome and a more efficient simulation model was built, allowing for the measurement and standardization of the associated process operations.